Does Bank Health Affect Sharia Bank Financing in The Satellite City of Jakarta? - Suko Wiryanto, Fadhli; Yetty, Fitri; Nopiyanti, Anita (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
Various factors can influence the size of distribution financing in banking. To monitoring for existence The company continues financing distribution can be allocated appropriately optimally, banks need to pay attention to internal factors in assessing the level of health banks that can influence the distribution of financing. Internal bank health assessment This research is based on POJK No.8/POJK.03/2014 using bank health assessments with a risk approach (RGEC), measurement focuses on quantitative measurements use financial ratios, financial reports, therefore the variables are used are NPF, ROA, and CAR. The annual reports of the 3 largest Sharia Banks in Depok City were used as research samples. By method secondary data collection using multiple linear analysis and SPSS for data analysis. The research results show that NPF, ROA and CAR are partially positive haven’t a significant influence but simultaneously has quite a significant influence towards the distribution of financing at Depok’s Sharia Banks.